MITIGASI BENCANA TSUNAMI DI SDN TIRTOHARGO DUSUN BAROS, DESA TIRTOHARGO, KECAMATAN KRETEK, KABUPATEN BANTUL, PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Danis Agoes Wiloso; Septian Vienastra (JURNAL GAUNG INFORMATIKA, 2018)
The Aceh tsunami disaster in 2004 made Indonesians aware of the dangers of the tsunami, especially in the coastal areas. Emergency preparedness and tsunamiunderstanding need to be socialized to the population from an early age. Understanding the occurrence of a tsunami disaster needs to be socialized to the community, if there is an earthquake and the epicenter is in the sea followed by sea water subsidence then the population must stay away from the beach.One of the efforts made is the socialization to elementary school students so that later can be transmitted to their offspring will be dangerous tsunami disaster andmitigation efforts so that will reduce the risk factor when the tsunami hit the area.In the socialization of community service at SDN Tirtohargo Dusun Baros, described how the tsunami, early warning system and mitigation efforts. One of themitigation efforts of the tsunami disaster is the mangrove planting around Baros Beach.